136k views
5 votes
Rewrite the function by completing the square h(x) =4x^2+4x+1​

User Nickolaus
by
5.6k points

2 Answers

4 votes

Answer:

Explanation:

4(x+1/2)^2+0

The first box is 4

The second box is 1/2

the third box is 0

User Kayne
by
4.9k points
6 votes

Answer:

4(x +
(1)/(2)

Explanation:

Given

h(x) = 4x² + 4x + 1

To complete the square the coefficient of the x² term must be 1

Factor out 4 from 4x² + 4x

h(x) = 4(x² + x) + 1

add/subtract ( half the coefficient of the x- term )² to x² + x

h(x) = 4(x² + 2(
(1)/(2) )x +
(1)/(4) -
(1)/(4) ) + 1

= 4(x +
(1)/(2) )² - 1 + 1

= 4(x +
(1)/(2)

User Damien Diederen
by
5.1k points